Optimization of external power delivering system of object by mechanical influence on the work of power line wires - Shesterenko, Volodymyr; Mashchenko, Oleg; Romaniuk, Volodymyr (My University, 2018)
Робота присвячена дослідженню методів зменшення стріли провисання проводів ліній електропередач (ЛЕП) за допомогою термокомпенсуючих пристроїв, розглянуті види та будова активних термокомпенсуючих пристроїв, розроблених авторами. Використовувались математичні моделі, які характеризують роботу проводів ЛЕП. Доведено, що компенсація стріли провисання проводів ЛЕП за допомогою активних термокомпенсаторів, виготовлених зі сплаву з ефектом пам’яті форми, дозволяє знижувати висоту опор при збереженні наявних прогонів чи зменшити кількість опор. Показана перевага активних термокомпенсаторів стріли провисання відносно наявних розробок. Наукова новизна полягає в дослідженні впливу активних термокомпенсаторів на роботу проводу повітряних ЛЕП.

The work is devoted to the research of methods of decreasing the sag of the power lines wires using thermo-compensating devices. This work contains a review of types and structures of active thermal compensating devices. Mathematical models that characterize the work of power line wires were used. Proven, that compensation of power line wires sag by using active thermal compensation devices, that are made of alloy with “shape memory effect” creates conditions under which it is possible either to increase spans, or to reduce the height of the transmission towers, while preserving the existing estimated spans. The advantage of active thermal compensation devices of power line arc of sagging over existing inventions was shown. Scientific novelty of this work consists in research of influence of active thermal compensation devices on work of overhead power line wire.
Keywords: повітряна лінія електропередавання; стріла провисання; напруга; overhead power line; sag; voltage; кафедра електропостачання і енергоменеджменту